The Effect of Financial Performance on Financial Distress - Azizah, Syawalia; Lismawati, Lismawati (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to examine the effect of financial performance on financial distress with corporate governance as a moderating variable in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The purposive sampling method was used in determining the research sample, so there were 42 companies and a total of 126 samples. The data analysis technique uses multiple linear regression analysis. The results of this study are capital adequacy and profitability have a negative effect on financial distress. Meanwhile, credit risk and corporate governance have a positive effect on financial distress. In addition, corporate governance is unable to strengthen and weaken the relationship of capital adequacy and credit risk to financial distress. However, the relationship between profitability and financial distress is weakened by corporate governance as moderation.